The Consequences of Lipid Profile in Menopausal Age - A Clinical Evaluation: The Consequences of Lipid Profile in Menopausal Age - A Clinical Evaluation - Trivedi, Rujuta; Pandya, Meera (National Journal of Integrated Research in Medicine, 2018)
Background: Menopause is an Oestrogen deficient state but unlike other hormone deficient states which are considered a disease, menopause is not a disease. Post-menopausal stage increases the chances of CHD due to deficiency of Oestrogen which among young women naturally helps to keep lipid profile normal. Method:This study is designed to evaluate the effect of menopause on cholesterol profile and its variation by administrating Shatavaryadivati. 43 patients with age between 40 to 60 years, who have cessation of Menstruation since one year, were selected for the study. Result: After administration of Shatavaryadivati, Serum cholesterol level was decreased up to 6.05% but it was non-significant at P >0.05, Serum triglyceride level was decreased up to 9.16% but it was insignificant at P>0.05 and HDL level was increased up to 4.37% which was significant at P <0.05. Conclusion: Data leads to positive results on lipid profile. Hence the administration of Shatavaryadivati helps to maintain the level of lipid profile in menopause. [Rujuta T NJIRM 2017; 8(4):45-47]